Data-Driven Approaches To Information Access - Dumais, Susan (Cognitive Science, 2003)
This paper summarizes three lines of research that are motivated by the practical problem of helping users ﬁnd information from external data sources, most notably computers. The application areas include information retrieval, text categorization, and question answering. A common theme in these applications is that practical information access problems can be solved by analyzing the statistical properties of words in large volumes of real world texts. The same statistical properties constrain human performance, thus we believe that solutions to practical information access problems can shed light on human knowledge representation and reasoning.